2009
DOI: 10.1002/jmv.21279
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection and genotyping of human papillomavirus in cervical carcinoma biopsies in an area of high incidence of cancer from Moroccan women

Abstract: Cervical cancer is a leading cause of cancer-related deaths in developing countries, and the human papillomavirus (HPV) is linked etiologically to cervical cancer. Eighty nine cervical carcinoma biopsies collected from women visiting the Oncologic Center in Casablanca (Centre Hospitalier Universitaire Ibn Rochd, Morocco) for cervical cancer symptoms, were screened for HPV DNA by polymerase chain reaction amplification with subsequent typing by hybridization with specific oligonucleotides for HPV types 16, 18, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 40 publications
6
27
1
1
Order By: Relevance
“…The second prevalent HPV type detected in our NPC biopsies is HPV59 (16,7%). Of interest, HPV-16 and -18, which are the most virulent genotypes associated with CC in Moroccan woman (35% to 45%) [21,22], were detected in very few Moroccan NPC cases (8.3%), and similar data were reported in an Iranian study [23]. …”
Section: Discussionsupporting
confidence: 64%
“…The second prevalent HPV type detected in our NPC biopsies is HPV59 (16,7%). Of interest, HPV-16 and -18, which are the most virulent genotypes associated with CC in Moroccan woman (35% to 45%) [21,22], were detected in very few Moroccan NPC cases (8.3%), and similar data were reported in an Iranian study [23]. …”
Section: Discussionsupporting
confidence: 64%
“…The second prevalent HPV type detected in Moroccan NPC biopsies is HPV59 (16,7%). Of interest, HPV-16 and -18, which are the most virulent genotypes associated with CC in Moroccan woman (35% to 45 %) (Khair et al 2009), were detected in very few NPC cases (8.3 %), and similar data were reported in an Iranian study (Mirzamani et al 2006). However, a recent study suggests that WHO-I NPC may be associated with oncogenic HPV.…”
Section: Wwwintechopencomsupporting
confidence: 73%
“…This result seems to be in line with previous reports [36,44]. In contrast, this molecular epidemiology profile was not consistent with observed in HIV-negative women [6][7][8] or women with CC in Morocco [9][10][11][12], in whom HPV 16 and 18 predominate. Such discrepancies between groups (HIVpositive and HIV-negative) has been reported in previous studies and may partly due to immune system deficiency [30,45].…”
Section: Discussioncontrasting
confidence: 39%
“…Previous studies in Moroccan women have been reported an inconsistent prevalence of HPV with 15.7% [6] in Rabat and 42.5-43.1% in Fez region [7,8]. However, the prevalence was much higher, ranging from 62% to 92%, among Moroccan women with CC [9][10][11][12]. The joint United Nations Programme on HIV/AIDS (UNAIDS) estimated that 30,000 (22,000 -40,000) Moroccans were living with HIV/AIDS at 2012, and women aged 15 years old and older living with HIV was 11,000 (8,500 -14,000).…”
Section: Introductionmentioning
confidence: 62%